2x+10-x=2(2x-6)

Simple and best practice solution for 2x+10-x=2(2x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+10-x=2(2x-6) equation:


Simplifying
2x + 10 + -1x = 2(2x + -6)

Reorder the terms:
10 + 2x + -1x = 2(2x + -6)

Combine like terms: 2x + -1x = 1x
10 + 1x = 2(2x + -6)

Reorder the terms:
10 + 1x = 2(-6 + 2x)
10 + 1x = (-6 * 2 + 2x * 2)
10 + 1x = (-12 + 4x)

Solving
10 + 1x = -12 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
10 + 1x + -4x = -12 + 4x + -4x

Combine like terms: 1x + -4x = -3x
10 + -3x = -12 + 4x + -4x

Combine like terms: 4x + -4x = 0
10 + -3x = -12 + 0
10 + -3x = -12

Add '-10' to each side of the equation.
10 + -10 + -3x = -12 + -10

Combine like terms: 10 + -10 = 0
0 + -3x = -12 + -10
-3x = -12 + -10

Combine like terms: -12 + -10 = -22
-3x = -22

Divide each side by '-3'.
x = 7.333333333

Simplifying
x = 7.333333333

See similar equations:

| 13-x=x^2+1 | | 73=0.7-4 | | 32=4a+19 | | 8(s-92)=32 | | 4(2)+3(-3)=-1 | | kx^2-36x=36 | | 1-(3/2-5x)=-2/5-2x | | 94y^2+56y=0 | | -3x-9=20-4x | | -128=4(4-6x) | | -5x+3-7x-1= | | 16+4h=36 | | -1(-6x+3)=9 | | 5000=x/706.85 | | 1.5/2.5=3/x | | 5000=x/(225π) | | (7n-35)(5n-4)=0 | | 5ix+3x= | | 3ix+5x= | | -m-1=6m+9 | | 1/2*p=377 | | 4x-10=6x+4 | | X-0.1X=320595 | | 13+y=16+13 | | X^2+10x-84=180 | | 2y=4*2-2 | | 2y=4*5-2 | | 13x=-x^2-40 | | 44n^2+28n=0 | | 2y=4*-2-2 | | 10/11x=220 | | [h/5]^2 |

Equations solver categories